Mapping of tms8 gene for temperature-sensitive genic male sterility (TGMS) in rice (Oryza sativa L.) - Hussain, Appibhai J.; Ali, Jauhar; Siddiq, Ebrahimali A.; Gupta, Vidya S.; Reddy, Umesh K.; Ranjekar, Prabhakar K. (Plant Breeding, 2012)
Genetic analysis of F-2 and backcross populations of an induced temperature-sensitive genic male sterility (TGMS) mutant source F 61 with normal pollen parents revealed that TGMS trait was controlled by a single recessive gene. Molecular tagging of TGMS trait was attempted using polymorphic randomly amplified polymorphic DNA (RAPD) and simple sequence repeats (SSR) markers through bulked segregant analysis. The RAPD primers UBC 345830, UBC 313927, microsatellites RM224 and RM21 produced putative markers, which differentiate parents and bulks from sterile parent and sterile bulks. The RAPD analysis of individual F-2 plants with the primer UBC345(830) showed perfect marker-phenotype cosegregation. The 830-bp RAPD fragment, which segregated with TGMS locus at a distance of 1.33 cM, was eluted and cloned, and sequence information was used for designing sequence-characterized amplified region (SCAR) primer, which cosegregated with TGMS locus at a distance of 0.8 cM. TGMS locus was mapped onto chromosome 11 using RM21 and RM224, flanking it at a distance of 4.3 and 3.0 cM, respectively. The DNA markers tightly linked to TGMS gene (tms8) in F 61 can be cost effectively used for marker-assisted selection of TGMS trait.
Keywords: Bulked segregant analysis; randomly amplified polymorphic DNA; rice; sequence-characterized amplified region; SSR; temperature-sensitive genic male sterility

Reference quality genome sequence of Indian pomegranate cv. `Bhagawa' (Punica granatum L.) - Roopa Sowjanya, P.; Shilpa, Parashuram; Patil, Goudappa Prakash; Babu, Dhinesh Karuppannan; Sharma, Jyotsana; Sangnure, Vipul R.; Mundewadikar, Dhananjay M.; Natarajan, Purushothaman; Marathe, Arvind Rajiv; Reddy, Umesh K.; Singh, Vikram Nripendra (Frontiers in Plant Science, 2022)
Pomegranate is an important fruit crop for ensuring livelihood and nutrition security in fragile semi-arid regions of the globe having limited irrigation resources. This is a high-value, nutritionally rich, and export-oriented agri-commodity that ensures high returns on investment to growers across the world. Although it is a valuable fruit crop, it has received only a limited genomics research outcome. To fast-track the pomegranate improvement program, de novo whole-genome sequencing of the main Indian cultivar `Bhagawa' was initiated by the Indian Council of Agricultural Research-National Research Center on Pomegranate (ICAR-NRCP). We have demonstrated that a combination of commercially available technologies from Illumina, PacBio, 10X Genomics, and BioNano Genomics could be used efficiently for sequencing and reference-grade de novo assembly of the pomegranate genome. The research led to a final reference-quality genome assembly for `Bhagawa' of 346.08 Mb in 342 scaffolds and an average N50 of 16.12 Mb and N90 of 1088.62 Kb. This assembly covered more than 98% of the estimated pomegranate genome size, 352.54 Mb. The LTR assembly index (LAI) value of 10 and 93.68% Benchmarking Universal Single-Copy Orthologs (BUSCO) completeness score over the 1,440 ortholog genes of the completed pomegranate genome indicates the quality of the assembled pomegranate genome. Furthermore, 29,435 gene models were discovered with a mean transcript length of 2,954 bp and a mean coding sequence length 1,090 bp. Four transcript data samples of pomegranate tissues were mapped over the assembled `Bhagawa' genome up to 95% significant matches, indicating the high quality of the assembled genome. We have compared the `Bhagawa' genome with the genomes of the pomegranate cultivars `Dabenzi' and `Taishanhong.' We have also performed whole-genome phylogenetic analysis using Computational Analysis of Gene Family Evolution (CAFE) and found that Eucalyptus grandis and pomegranate diverged 64 (60-70) million years ago. About 1,573 protein-coding resistance genes identified in the `Bhagawa' genome were classified into 32 domains. In all, 314 copies of miRNA belonging to 26 different families were identified in the `Bhagawa' genome. The reference-quality genome assembly of `Bhagawa' is certainly a significant genomic resource for accelerated pomegranate improvement.
Keywords: genome sequencing; hybrid genome assembly; Long Terminal Repeats Assembly Index (LAI); PacBio; pomegranate